2002
DOI: 10.1002/ajmg.10614
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of severe cholestatic hepatopathy in COACH syndrome

Abstract: COACH syndrome is a disorder with cerebellar vermis hypoplasia, oligophrenia, ataxia, coloboma, and hepatic fibrosis. Sixteen cases with certain COACH diagnosis have been reported so far. Neurologic abnormalities are the first symptoms in most cases. The majority of cases were diagnosed late in childhood or adolescence. Complications of the hepatopathy contribute extensively to the morbidity and lethality in the course of the disease. Major complications are portal hypertension, esophageal varices, and gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Most cases of COACH syndrome are accompanied with dysplastic renal disease, such as fibrocystic renal disease, atrophic tubules, and tubular basement membrane thickening (10). Foell et al(16) showed that 70% of COACH syndrome has renal abnormalities, and it may clinically manifest only in adulthood like our case (8, 10) (Table 1).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Most cases of COACH syndrome are accompanied with dysplastic renal disease, such as fibrocystic renal disease, atrophic tubules, and tubular basement membrane thickening (10). Foell et al(16) showed that 70% of COACH syndrome has renal abnormalities, and it may clinically manifest only in adulthood like our case (8, 10) (Table 1).…”
Section: Discussionmentioning
confidence: 53%
“… 1, Foell et al (16); 2 and 3, Wiesner et al (19); 4 and 5, Kumar and Rankin (14); 6, Barzilai et al (15); 7 and 8, Thompson and Baraitser (11); 9 and 10, Dietrich and Straub (10); 11, 12 and 13, Verloes and Lambotte (8); 14 and 15, Gentile et al (13); 16 and 17, Hunter et al (9); 18, Herzog et al (17); 19, Kirchner et al (18); 20, Baylor University Medical Center. …”
Section: Case Reportmentioning
confidence: 98%
See 1 more Smart Citation
“…Autosomal recessive polycystic kidney disease is associated with congenital hepatic fibrosis, but the renal cysts differ from the cystic disease in MKS and involve collecting ducts, maintaining the reniform appearance of the kidney on gross inspection [32]. The COACH syndrome includes cerebellar vermis hypoplasia, oligophrenia, ataxia, coloboma, and hepatic fibrosis [33,34].…”
Section: Discussionmentioning
confidence: 99%